2021
DOI: 10.1021/acs.analchem.0c04081
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Electric Field-Enhanced In-Source Declustering in High-Pressure Photoionization/Photoionization-Induced Chemical Ionization Mass Spectrometry for Operando Catalytic Reaction Monitoring

Abstract: Photoionization mass spectrometry (PI-MS) is a powerful and highly sensitive analytical technique for online monitoring of volatile organic compounds (VOCs). However, due to the large difference of PI cross sections for different compounds and the limitation of photon energy, the ability of lamp-based PI-MS for detection of compounds with low PI cross sections and high ionization energies (IEs) is insufficient. Although the ion production rate can be improved by elevating the ion source pressure, the problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The evolution of intensity as a function of U hexapole – U skimmer is shown in Figure b, which revealed that a strong electric field between hexapole rods and the skimmer is beneficial for ion focusing. Similar results were also observed in another work . In the following experiments, the optimized RF and DC voltage was set to be 400 V pp and 7 V, respectively.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The evolution of intensity as a function of U hexapole – U skimmer is shown in Figure b, which revealed that a strong electric field between hexapole rods and the skimmer is beneficial for ion focusing. Similar results were also observed in another work . In the following experiments, the optimized RF and DC voltage was set to be 400 V pp and 7 V, respectively.…”
Section: Resultssupporting
confidence: 78%
“…Similar results were also observed in another work. 39 In the following experiments, the optimized RF and DC voltage was set to be 400 V pp and 7 V, respectively.…”
mentioning
confidence: 99%
“…The peak intensity of [EC + H] + rapidly increased when the acetone concentration increased from 0 to 200 ppmv, which was obviously attributed to production of more protonated acetone ions. The peak intensity of [EC + H] + then decreased when the acetone concentration was further increased from 200 to 1000 ppmv because more cluster ions [(C 3 H 6 O) n + H] + generated at higher concentrations of acetone and the reaction capacities for the reactions of [(C 3 H 6 O) n + H] + with EC molecules decreased. , Therefore, the optimal concentration of acetone was 200 ppmv. M false( analyte false) + h ν normalM + + normale normalM + + normalX false[ normalM + normalH false] + + false[ normalX normalH false] C 3 H 6 O + h ν normalC 3 normalH 6 normalO + + normale normalC 3 normalH 6 normalO + + normalX false[ normalC 3 normalH 6 normalO + normalH false] + …”
Section: Resultsmentioning
confidence: 99%
“…The peak intensity of [EC + H] + then decreased when the acetone concentration was further increased from 200 to 1000 ppmv because more cluster ions [(C 3 H 6 O) n + H] + generated at higher concentrations of acetone and the reaction capacities for the reactions of [(C 3 H 6 O) n + H] + with EC molecules decreased. 44,45 Therefore, the optimal concentration of acetone was 200 ppmv.…”
Section: Signal Intensities Of [Ea + H] 13cmentioning
confidence: 99%
“…[24][25][26] However, limited by the photon energy, which is usually below 10.6 eV, some low molecular weight VOCs, e.g., acetonitrile, with an ionization energy (12.2 eV) above the photon energy are hard to detect by PI-MS. To overcome this problem, a series of dopant-assisted photoionization techniques have been developed to broaden the range of detection targets and enhance the detection efficiency of PI-MS for specic VOC species. [27][28][29][30][31][32][33] The dopantassisted photoionization technique is actually photoinduced chemical ionization such as charge transfer, proton transfer, substitution, etc.…”
Section: Introductionmentioning
confidence: 99%